2010
DOI: 10.1016/j.cellsig.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

WNT1-inducible signaling pathway protein-1 activates diverse cell survival pathways and blocks doxorubicin-induced cardiomyocyte death

Abstract: The anthracycline antibiotic doxorubicin (DOX) is a potent cancer chemotherapeutic agent that exerts both acute and chronic cardiotoxicity. Here we show that in adult mouse cardiomyocytes, DOX activates (i) the pro-apoptotic p53, (ii) p38MAPK and JNK, (iii) Bax translocation, (iv) cytochrome c release, and (v) caspase 3. Further, it (vi) inhibits expression of anti-apoptotic Akt, Bcl-2 and Bcl-xL, and (vii) induces internucleosomal degradation and cell death. WNT1-Inducible Signaling Pathway Protein-1 (WISP1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(145 citation statements)
references
References 56 publications
(93 reference statements)
7
138
0
Order By: Relevance
“…For example, WISP1, an effector of activated Wnt signaling previously reported to regulate cell survival, [17][18][19] showed the highest level change (3.6-fold higher in U373-IR than in U373-C). Patient data at the US National Cancer Institute (Repository of Molecular Brain Neoplasia Data (REMBRANDT) 20,21 ) also indicated that upregulation of WISP1 is associated with poorer clinical outcome (Supplementary Figure S2), further substantiating our data.…”
Section: Microarray Analysis Reveals Upregulated Wnt Signaling In U37mentioning
confidence: 99%
“…For example, WISP1, an effector of activated Wnt signaling previously reported to regulate cell survival, [17][18][19] showed the highest level change (3.6-fold higher in U373-IR than in U373-C). Patient data at the US National Cancer Institute (Repository of Molecular Brain Neoplasia Data (REMBRANDT) 20,21 ) also indicated that upregulation of WISP1 is associated with poorer clinical outcome (Supplementary Figure S2), further substantiating our data.…”
Section: Microarray Analysis Reveals Upregulated Wnt Signaling In U37mentioning
confidence: 99%
“…Although multiple cellular pathways may account for the cytoprotective capacity of WISP1 [7,8,10,11,20,21], recent work suggests that mTOR may play a significant role in providing cellular protection with WISP1 [13]. Yet, cellular protection by mTOR may require a level of modulation since high mTOR activity has been associated with apoptotic cell death [43].…”
Section: Discussionmentioning
confidence: 99%
“…WISP1 has been demonstrated to rely upon the phosphorylation and activation of phosphatidylinositol-3-kinase (PI 3-K) and protein kinase B (Akt) [7,8,10,11,20,21] as well as the mammalian target of rapamycin (mTOR) [13] to promote cellular protection. In addition, mTOR phosphorylates and activates p70S6K at threonine 389 and is a marker of mTOR activity [40].…”
Section: Wisp1 Modulates the Post-translational Phosphorylation Of Akmentioning
confidence: 99%
See 2 more Smart Citations